Mediation effect of locus of control and government policy on the relationship between transformational leadership, entrepreneurship and performance - Ma, Tin Cho Mar (2015)
This study was designed to determine the relationship between transformational leadership, entrepreneurship, performance in SMEs Malaysia. The concept of entrepreneurship has emerged recently in entrepreneurship literature especially in explaining transformational leadership behavior as a counterpart of the process of organizational performance. Transformational leadership and entrepreneurship regularly play a dominant role as one of the major factors influencing relationships in the entrepreneur dyad and facilitates the process of higher performance by imparting access to the international market venturing. Thus, this study concerns transformational leadership, entrepreneurship and entrepreneur performance in SMEs Malaysia. This critical entrepreneur relationship and its animating factors are, however, overlooked and largely neglected in the literature. Accordingly, it is inconclusive as to which factors influence higher performance and how they influence it. Drawing on the literature, this study strived and investigated the spectrum of entrepreneur and has explicitly examined eight factors influencing performance to entrepreneur by integrating the factors in a comprehensive model. Theoretical foundations were drawn basically from contingency theories of situational theory, leadership theory and entrepreneurship theory of the firm to design a basic framework for quantitative investigation. Further, the study endeavored to gain important insights into the phenomena related to the leadership, entrepreneurship and performance process through quantitative primary data. In addition, to validate the competing model is developed where locus of control and government policy play mediating role for some of the predictor variables in the model. Primary data were collected from a sample 425 SMEs Malaysia for empirical verification of the quantitative models using Structural Equation Modeling (SEM) together with the descriptive statistical method was used to illustrate structural points. However, the analysis of the modified proposed structural model revealed that hypotheses were tested including direct paths as antecedents of performance. As reported in this study, the proposed model with minor modifications fit better with the data compared to competing model, and it explained 52% of the variance of performance. However, the analysis of the modified proposed structural model revealed that twelve hypotheses were validated including eight direct paths as antecedents of entrepreneur performance. The mediating role of trust and opportunism in the model is also supported. The findings of descriptive study showed that the majority of the respondents were female (51%) follow by the male (49%). The majority of respondent ages are from 31-43 years old. This study showed that (32%) of the respondents are Doctorate Degree graduated, followed by (26%) from Undergraduate program and (24%) were with Master Degree and the lowest from MBA Degree was (19%). The findings supported most conceptual links in the quantitative model and lend supports to twelve hypothesized relationships in the modified structural model. These findings extended the application of the underpinned theories and their tenets in explaining the entrepreneur performance and contributed to the body of knowledge. Implications of the findings were discussed and future research directions were recommended. This study provides effective assistance for SMEs Malaysia embarking to improve their performance. Also this study represents a knowledge gap and offers practical help to SMEs Malaysia to leverage the skills and expertise of their organizational members and consequently to maintain and enhance their performance.